The death of the Internet - Jakobsson, Markus; ebrary, Inc. (Hoboken, N.J. : IEEE Press, Computer Society, Wiley, Higher Education Press, 2012)
"Fraud poses a significant threat to the Internet. 1.5% of all online advertisements attempt to spread malware. This lowers the willingness to view or handle advertisements, which will severely affect the structure of the web and its viability. It may also destabilize online commerce. In addition, the Internet is increasingly becoming a weapon for political targets by malicious organizations and governments. This book will examine these and related topics, such as smart phone based web security. This book describes the basic threats to the Internet (loss of trust, loss of advertising revenue, loss of security) and how they are related. It also discusses the primary countermeasures and how to implement them"--
pt. 1. The problem -- pt. 2. Thinking about solutions.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Internet -- Security measures; Electronic commerce -- Security measures; Data protection; Computer crimes; Electronic books